Using a Mobile Application for Real-Time Collection of Patient-Reported Outcomes in Hepatopancreatobiliary Surgery within an ERAS® Pathway. Issue 8 (August 2019) - Pickens, Ryan; Cochran, Allyson; Tezber, Kendra; Berry, Renna; Bhattacharya, Emily; Koo, Denice; King, Lacey; Iannitti, David A.; Martinie, John B.; Baker, Erin H.; Ocuin, Lee M.; Hunt, Jarrett; et al.
Patient-reported outcomes (PROs) are essential for patient-centered health care. This pilot study implemented a mobile application customized to an hepatopancreatobiliary Enhanced Recovery After Surgery (ERAS®) program—a novel environment—for real-time collection of PROs, including ERAS® pathway compliance. Patients undergoing hepatectomy, distal pancreatectomy, or pancreaticoduodenectomy through the ERAS® program were prospectively enrolled over 10 months. The application provided education and questionnaires before surgery through 30 days postdischarge. Thresholds were set for initial adoption of the application (75%), PRO response rate (50%), and patient satisfaction (75%). Daily postdischarge health checks integrated customized responses to guide out-of-hospital care. Of 165 enrolled patients, 122 met inclusion criteria. Application adoption was 93 per cent (114/122) and in-hospital engagement remained high at 88 per cent (107/122). Patients completed 62 per cent of PRO on quality of life, postoperative pain, nausea, opioid consumption, and compliance to ERAS® pathway items, including ambulation and breathing exercises. During postcharge tracking, 12 patients reported that the application prevented a phone call to the hospital and three patients reported prevention of an emergency room visit. PRO collection through this mobile device created an integrated platform for comprehensive perioperative care, patient-initiated outcome tracking with automatic reporting, and real-time feedback for process change. Improving proactive outpatient management of complex patients through mobile technology could help restructure health-care delivery and improve resource utilization for all patients.